2020
DOI: 10.1177/1035304620981405
|View full text |Cite
|
Sign up to set email alerts
|

Work scheduling and work location control in precarious and ‘permanent’ employment

Abstract: This article explores the relationship between precarious employment and seafarers’ control over the scheduling and location of their work, and considers the implications of this relationship for their occupational health and safety. Semi-structured interviews were carried out with 20 permanently and 17 precariously employed seafarers. In contrast with those on permanent contracts, seafarers employed by crewing agencies on temporary contracts were deployed at short notice and commenced work on vessels irrespec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Participants in several studies reported feelings of uncertainty and insecurity—for example, seafarers on temporary contracts reported multiple forms of work scheduling uncertainty including being deployed at short notice, commencing work on vessels irrespective of whether they had had adequate rest and restoration period at home, often having to board unfamiliar vessels without having familiarisation training, unstable work teams, and a mismatch between actual and expected tour of duty durations due to mandatory tour extensions [ 77 ]. In the same study, participants perceived that scheduling and location uncertainties were closely linked with increased risks to safety and wellbeing, which was perceived to be particularly poor when both work location and task uncertainty were experienced together.…”
Section: Resultsmentioning
confidence: 99%
“…Participants in several studies reported feelings of uncertainty and insecurity—for example, seafarers on temporary contracts reported multiple forms of work scheduling uncertainty including being deployed at short notice, commencing work on vessels irrespective of whether they had had adequate rest and restoration period at home, often having to board unfamiliar vessels without having familiarisation training, unstable work teams, and a mismatch between actual and expected tour of duty durations due to mandatory tour extensions [ 77 ]. In the same study, participants perceived that scheduling and location uncertainties were closely linked with increased risks to safety and wellbeing, which was perceived to be particularly poor when both work location and task uncertainty were experienced together.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the findings add to concerns about the adequacy and effectiveness of international regulations concerning seafarers’ working conditions. One such issue is the use of crewing agencies to recruit seafarers on single voyage contracts [14] . Seafarers under such contractual arrangements are more likely to feel compelled to accept unfavorable employment conditions and/or extensions to their tour of duty, with increased risk of poor health and safety outcomes [14] , [38] .…”
Section: Discussionmentioning
confidence: 99%
“…One such issue is the use of crewing agencies to recruit seafarers on single voyage contracts [14] . Seafarers under such contractual arrangements are more likely to feel compelled to accept unfavorable employment conditions and/or extensions to their tour of duty, with increased risk of poor health and safety outcomes [14] , [38] . Another issue, highlighted in a recent study [55] , are systemic failures in the implementation of current regulations on seafarers’ work and rest hours.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study add to a growing body of literature which explores the experiences of the seafaring workforce during the COVID-19 pandemic. Previous research (see, for example, Devereux and Wadsworth 2020) has indicated that precarious employment negatively impacts on the health, safety and well-being of those who work at sea. The findings of the study described in this paper indicate that the pandemic has served to widen this gap between employment types and that those with the weakest employment relationships have experienced the greatest challenges.…”
Section: Discussionmentioning
confidence: 99%